The Transition to Renewable Energy - Charles F. Mason; Rémi Morin Chassé (Center for Economic Studies and ifo Institute (CESifo), 2018)
The existing economics literature neglects the important role of capacity in the production of renewable energy. To fiill this gap, we construct a model in which renewable energy production is tied to renewable energy capacity, which then becomes a form of capital. This capacity capital can be increased through investment, which we interpret as arising from the allocation of energy, and which therefore comes at the cost of reduced general production. Requiring societal well-being to never decline, we describe how society could optimally elect to split energy in this fashion, the use of non-renewable energy resources, the use of renewable energy resources, and the implied time path of societal well-being. Our model delivers an empirically satisfactory explanation for simultaneous use of non-renewable and renewable energy. We also discuss the optimality of ceasing use of non-renewable energy before the non-renewable resource stock is fully exhausted.
Keywords: C61; Q42; Q56; 330; sustainability; energy; resource use